A 6 months retrospective observational study to assess the rationality and effectiveness of snake bite management in a tertiary care teaching hospital of rural Bengal, India - Dan, Satrajit; Mandal, Ananya; Das, Abhijit; Chakrabarty, Sourav; Gangopadhyay, Tanmoy (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Snake envenomation is a common life-threatening problem encountered all-over West Bengal particularly in the rural areas. There are a large number of patients attending the Emergency unit and being admitted to the Medicine ward, some in the intensive care unit (ICU) and intensive therapy unit (ITU) of the tertiary health care facilities. The objective of this study was to assess rationality and effectiveness of management of venomous snake bite following standard protocol – Standard treatment guidelines of Government of West Bengal and National snakebite management protocol of Government of India. Methods: This was a retrospective observational study of six months (May - October 2017) duration. Data were collected from the treatment records of patients admitted with history of snake bite in the Medicine ward, ICU and ITU of tertiary care teaching hospital of rural Bengal. Results: Of the 63 venomous bite patients, most (82.5 %) were diagnosed to have features of neurotoxic envenomation. All of them (100%) received anti-snake venom (ASV). There was no incidence of anaphylactic reaction as well as any serious adverse drug reaction following ASV administration. Two patients developed acute renal failure, needed haemodialysis. Overall percentage of mortality was 3.2%. Conclusions: The survival rate in venomous snake bite is found to be high in this institution. The practice of snake bite management is found to be adherent with standard protocol. A multicentric study of longer duration is suggested to draw a firm conclusion.